Simulation of daily diurnal variations of creep and shrinkage in concrete building - Li, An (2014)
This project was conducted to simulate and analyse the daily creep and shrinkage effects in concrete building in Singapore. Monthly and yearly creep and shrinkage effects are also taken into account.